Multi-objective tribological and energy optimization of an automatic valve lapping machine using a hybrid RSM NSGA-II approach - Reinaldi Teguh Setyawan; Ery Muthoriq; Syahrizal Syahrizal (Politeknik Negeri Lhokseumawe, 2026)
Optimizing valve seat reconditioning requires balancing sealing performance, surface integrity, energy consumption, and component wear within practical workshop constraints. This study presents the design, development, and multi-objective optimisation of a low-cost automatic valve lapping system using a hybrid Response Surface Methodology (RSM) and Non-dominated Sorting Genetic Algorithm II (NSGA-II) framework. A prototype automatic valve lapping rig was developed by integrating a DC-motor-driven spindle with adjustable spring loading and an Arduino-based control and data-acquisition system, enabling controlled variation of spindle speed (300–600 rpm) and axial load (60–140 N). Leakage time, surface roughness (Ra), electrical energy consumption, and valve wear volume were measured using a three-level factorial design. Quadratic response surface models with satisfactory statistical adequacy were established for all responses. The RSM models were employed in NSGA-II to maximise leakage time and minimise surface roughness, energy consumption, and wear, subject to practical operational constraints. The optimisation results reveal clear trade-offs between sealing quality, energy efficiency, and component life, and identify an optimal operating window of approximately 430–470 rpm and 90–110 N, providing a robust compromise solution and a practical operating map for workshop valve seat reconditioning.